Interpretation in Private International Law - Lima Pinheiro, LLuis de (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
The object of this essay is the methodology of legal interpretation in Private International Law. Private International Law is considered here as a legal subject that comprises Choice of Law, Jurisdiction and Recognition of Judgments. Besides general considerations, the specificity of the interpretation of domestic rules (in the Portuguese legal order) and of supranational rules (international and from the European Union) is addressed.The essay pleads for a wide identity of the specific issues arising from the interpretation of Private International Law provisions on the Choice of Law, Jurisdiction and Recognition of Judgments, which reinforces the justification for a broad view of the legal subject at stake.